2017
DOI: 10.1007/978-981-10-2305-7_12
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Trust in Mass Media and the Healthcare System and Individual Health: Evidence from the AsiaBarometer Survey

Abstract: Background: Vertical and horizontal trust, as dimensions of social capital, may be important determinants of health. As mass media campaigns have been used extensively to promote healthy lifestyles and convey health-related information, high levels of individual trust in the media may facilitate the success of such campaigns and, hence, have a positive influence on health. However, few studies have investigated the relationship between trust levels in mass media, an aspect of vertical trust, and health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Trust in health organizations, governments, and the media facilitates effective health communication. 161 The concept of trust includes several aspects of beliefs and feelings, such as credibility, security, and reliability 162 and is established through interactions in diverse social networks (e.g., family, friends, and acquaintances). An analysis of trust and its meaning for health care systems states that ''health systems are inherently relational and so many of the most critical challenges for health systems are relationship and behavior problems.''…”
Section: Culture and Trust In (Health) Organizations And Mediamentioning
confidence: 99%
“…Trust in health organizations, governments, and the media facilitates effective health communication. 161 The concept of trust includes several aspects of beliefs and feelings, such as credibility, security, and reliability 162 and is established through interactions in diverse social networks (e.g., family, friends, and acquaintances). An analysis of trust and its meaning for health care systems states that ''health systems are inherently relational and so many of the most critical challenges for health systems are relationship and behavior problems.''…”
Section: Culture and Trust In (Health) Organizations And Mediamentioning
confidence: 99%
“…Those with higher trust in media are more likely to accept health messages and to adopt health behaviors. The effects of trust in media on compliance of preventive measures is realized through increased acceptance of health-related messages (Tokuda et al, 2009). Media trust was found to associate with compliance with all the recommended behaviors in pandemic influenza H1N1 2009 (Prati et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, institutional trust is considered as a measure of support for, or sustainability of, the political systems and implementation of a wide range of policies (Boda & Medve-Balint, 2014;Newton & Zmerli, 2011). Social and institutional trust also appears to be significantly associated with people's quality of life and well-being (e.g., Ciziceno & Travaglino, 2019;Hudson, 2006;Piumatti et al, 2018;Thoresen et al, 2018;Tokuda et al, 2009;Yi, 2009). Thoresen et al (2018) found that institutional trust significantly decreased among the people who experienced a disaster; and that low trust in the police and legal system was significantly related to mental health problems, lack of social support, and lower life satisfaction among them.…”
mentioning
confidence: 99%
“…They further indicated that the relationship between institutional trust and life satisfaction was in part mediated by political interest. Tokuda et al (2009) showed that perceived health condition was significantly associated with trust in mass media (i.e., newspapers and TV) and the healthcare system among Asian populations. Sibley et al (2020) reported that, in the beginning of the lockdown in New Zealand, people's psychological distress level increased; meanwhile their trust in the government, politicians, police, national identity, and sense of community also increased compared to before the lockdown.…”
mentioning
confidence: 99%